Economic analysis of soybean-maize crop rotation in a no-tillage system - Faleiros, Gabriel Diniz; Santos, David Ferreira Lopes [UNESP]; Conceição, Elimar Veloso [UNESP]; Corá, José Eduardo [UNESP] (My University, 2020)
Brazil is one of the largest food suppliers in the world. The country faces new challenges to remain competitive considering the dynamism of Brazil´s agribusiness sector, with the need to balance agricultural production with environmental preservation. New technologies that result in sustainable production systems that provide yield gains are necessary. This study aims to economically analyse a conservationist system conducted during 10 consecutive years. The treatments were the combination of summer and winter crops under no-tillage system. The summer crop sequences (sown in October/November) were (i) continuous maize cultivation, (ii) continuous soybean, and (iii) soybean/maize rotation. The winter crops (sown in February/March) were (i) maize, (ii) sunflower, (iii) oilseed radish, (iv) pearl millet, (v) pigeon pea, (vi) grain sorghum, and (vii) sunn hemp, consisting of 21 treatments. An investment analysis was performed based on a discounted cash flow. The capital asset pricing model (CAPM) was used to define the discount rate. The data were extrapolated to a typical property of 50 hectares. The results indicate that the yield gain is significant in the conservationist system adopted and superior to that reported in the national average. The minimum attractiveness rate was high for all the treatments. The adoption of soybean and maize rotation, with maize as off-season provided the best economic alternative. The second best alternative is the soybean monoculture with maize as off-season, widely adopted in Brazil for its great agronomic benefit. In conclusion, the investment costs are high, making the small-scale production of soybean and maize not sustainable in the long term. Furthermore, an idleness of the defined machinery and labour capacity was observed. However, the production of maize or sunflower in the off-season resulted in a positive operational cash flow in all treatments.
Keywords: Alternative crops; Conservation agriculture; Farm management; Soybean. Maize